2022
DOI: 10.3390/ijerph192114042
|View full text |Cite
|
Sign up to set email alerts
|

Online Exercise Training Program for Brazilian Older Adults: Effects on Physical Fitness and Health-Related Variables of a Feasibility Study in Times of COVID-19

Abstract: The COVID-19 pandemic brought negative consequences such as social isolation and limited access to health services, especially for older adults. The objective was to evaluate effects of an online exercise training program and physical fitness and health-related variables on Brazilian older adults during the COVID-19 pandemic and secondarily to assess the feasibility and application of an online program. A study was developed with twenty older adults who participated in a 9-month online exercise program. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…By eliminating the need to travel, online fitness programs make exercise more accessible to those who participate. These findings corroborate the points made by da Silva et al [55], who stressed that the convenience of exercising at home, the ability to avoid adverse weather conditions, and not facing transportation issues are significant advantages. Porter et al [13] further suggest that convenience may lead older adults to favor the flexibility and accessibility of online options, even in the post-pandemic period.…”
Section: Perceived Usefulnesssupporting
confidence: 90%
“…By eliminating the need to travel, online fitness programs make exercise more accessible to those who participate. These findings corroborate the points made by da Silva et al [55], who stressed that the convenience of exercising at home, the ability to avoid adverse weather conditions, and not facing transportation issues are significant advantages. Porter et al [13] further suggest that convenience may lead older adults to favor the flexibility and accessibility of online options, even in the post-pandemic period.…”
Section: Perceived Usefulnesssupporting
confidence: 90%
“…Thus, communication technology tools and virtual environments make it possible to maintain an active lifestyle through supervised online physical training, which can be through video calls and exercises performed only with body weight 10 . In this sense, studies with remote training found a maintenance of depressive symptoms and quality of life 11 as well as an improvement in depressive symptoms compared to the control group 12 .…”
Section: Introductionmentioning
confidence: 90%
“…The effect size was set to 0.58, power value was set to 0.8 and 20 people were counted. For the effect size, reference was made to previous study [17]. In consideration of the dropout rate of 20% during the course of experiment, the number of participants was set to 24.…”
Section: Ethodsmentioning
confidence: 99%